Notary Role in Making of a Marriage Agreement for A Husband & Wife Couple in Divorce - Akrimni Nur Zakiyyah; Sri Endah Wahyuningsih (Sultan Agung Notary Law Review, 2021)
The existence of the institution of marriage is to legalize the legal relationship between a man and a woman. Due to the very important consequences of marriage, society needs a regulation of living together, namely regarding the conditions for the inauguration, implementation, continuation and termination of living together. However, it is unfortunate that many people in their domestic life end up in divorce. This is what people often use as the only way to end domestic conflicts, so that it has a negative impact on children or one of the divorced couples.Based on this description, this study aims to find out and analyze how the role of a notary in making a marriage agreement deed for a husband and wife in divorce and analyze how the function of a marriage agreement in a husband and wife in divorce. The research method in this thesis uses a sociological juridical approach with descriptive research specifications. Data sources and data collection methods used primary and secondary data which were analyzed qualitatively. The results of this study indicate that the authority of a notary in carrying out his duties and position as a notary is to make an authentic deed. The function of the marriage agreement deed in divorce is to respect and appreciate the dignity of each party and to ensure that there are limits to the rights and obligations that must be carried out by husband and wife, but in marriage there are provisions for the distribution of assets if a problem occurs in the future. if the parties wish that the joint property be included in the joint decision with a divorce dispute, the results to be obtained are for peace and the examination does not require many stages of examination as the examination of marital property in general which is not related or bound by a marriage agreement.